Uso pedagógico do blog no ensino-aprendizagem de espanhol: elaboração e avaliação de uma terefa - Lanza, Heloiza Helena (2007)
This study aims at searching for blogs, that could be used as Spanish language learning material, in the Spanish blogosphere as well as developing and evaluating a teaching material based on task learning concepts, for the pedagogical use of blogs. My intention, with this study, was to fill the gap related to the use of blog sin language teaching, especially in the Spanish language teaching. This work is based on the functional view of language teaching which guides the Parâmetros Curriculares Nacionais de Ensino Médio (Brasil, PCN-EM, 2000a) and the Orientações Curriculares para o Ensino Médio: Linguagens, Códigos e Suas Tecnologias (Brasil, Volume 1, 2006). The proposal for the pedagogical use of blogs is grounded on the theoretical concepts of task based learning (Nunan 1991; Willis, 1996 and Ellis 2003), material development and evaluation (Tomlinson, 1998; Graves, 2000; Leffa, 2003; Ramos 2003a e 2003b, among others) linked to the guidelines in PCN-Apresentação dos Temas Transversais e Ética (Brasil 2000) . In relation to the use of blogs for educational purposes, this study is based on the theoretical concepts by Oliveira 2006; Sáez Vacas 2005; Fumero, 2005; Orihuela, 2006 among others. This research is a qualitative one (Denzin & Lincoln, 1998) which makes use of documentary methodology (Gil, 1991; Pádua, 2004). The findings of this study include the presentation of a bank of blogs which can be used for the teaching and learning of Spanish as a foreign language; the presentation of a set of criteria for selecting blogs for pedagogical use; the design and evaluation of a task which makes use of blogs as teaching material allied to the theme Ethic proposed by the PCN Introdução aos Temas Transversais e Ética (Brasil, 2000)